Answer:
y = -3x + 2
Step-by-step explanation:
To find the slope of an equation you can do (y2-y1)/(x2-x1). Plug the values in from the equation and you get (-1+7)/(1-3), or 6/-2. This means the slope is -3. Then you plug the values of y and x into an equation y = -3x + b, and you get -1 = (-3)1 + b. Solve for b. -1 = -3 + b, (add 3 to each side) 2 = b. Then plug b back into your equation and you get y = -3x + 2
Answer:
cool thx for the points
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
Substitute n for 3
A(n) = 3/2(-2)^(n-1)
A(3) = 3/2(-2)^(3-1)
A(3) = 3/2(-2)²
A(3) = 3/2(4)
A(3) = 12/2
A(3) = 6
I can maybe help, what's the question
Answer:
x
=
−
500
b
−
50
a
+
R
±
√
250000
b
2
+
2500
a
2
−
100
a
R
+
1000
b
R
+
R
2
+
50000
a
b
2
a
b
Step-by-step explanation: